Vestidos tejidos a crochet y su incidencia en el desarrollo de la creatividad del área de corte y confección en el centro de formación artesanal “Armando Coronel Dreshner” del cantón el Empalme - Intriago Anchundia, Merly María (2016)
This was made with purpose of the craft dress crochet Center Craf training "Armando Coronel Dreshner" Canton El Empalme, in the area of cutting and sewing, in order to appreciate the theoretical field as practical here based on the initiative, dynamism and creativity to be imposed to understand and experience it, inspires me to make investigation in to the educational a wakening an interesting art and fully exercise the profession. Chapter I covers related to the idea or theme of Research, contextual framework, Context International Context National, local context, internal Institutional Context, problematics situation, problem statement, General problem, the sub-problems or derivatives, delimiting Research, justification, Research Objectives, General Objective Specific Objectives. Chapter II Theoretical framework, conceptual framework, referential framework on the issue: research, research Background, Analysis categories, theoretical position, hypothesis, general hypotheses, sub-hypotheses or derived variables. Results obtained Chapter III Research, Testing Applied Statistics, Data Analysis and Interpretation, general and specific conclusions, specific and general recommendations. Chapter IV Proposed Application of Results, alternative obtained, Scope alternative, Basics of alternative, background, justification, objectives, structure General of the Proposal, title, Components, Expected results of the alternative, bibliography, annexes Images crochet dress in combination with ateliers.